Early Breastfeeding Initiation Effect in Stunting: A Systematic Review - Steven Christian Susianto; Nina Rini Suprobo; Maharani Maharani (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Stunting has been a global burden worldwide, resulting in severe outcomes, including inadequate brain development until mortality. Early breastfeeding initiation as a global strategy affects the success of continuous breastfeeding that influences the children’s growth and development. This study aimed to provide a literature review on how early breastfeeding initiation might help children avoid stunting. Methods: We searched articles published from 2017 to 2022 in PubMed, Science Direct, Cochrane, and the Indonesia Database with keywords “Early breastfeeding initiation” OR “Early breastfeeding” OR” Early Initiation Breastfeeding” AND “stunting.” All data were gathered and analyzed. Results: A total of 12 articles from 6690 articles met the inclusion, exclusion, and eligibility criteria. The mean of early breastfeeding initiation was 61,82%, with the lowest study in Chimborazo and Tungurahua, Ecuador, and stunting was 33,07% as the highest prevalence was in Chimborazo and Tungurahua, Ecuador, while the lowest in Saharawi refugee camps, Algeria. The mean prevalence of children who did not get early breastfeeding initiation and stunting occurred at 40,85%, and eight studies reported that early breastfeeding initiation was associated with stunting. Conclusion: Early breastfeeding initiation can lower stunting risk in children. Early breastfeeding initiation ensures children obtain enough colostrum that enhances the children’s immunity and probability of exclusive breastfeeding, ensuring children obtain adequate nutritional intake and prevent stunting.